(untitled) (Scientia Agricola, 2019)
This research investigated the potential of beef products with acid whey to release bioactive peptides and thereby emphasize their health-promoting potential. Peptide sequences were isolated and identified by liquid chromatography-electrospray ionization-mass spectrometry (LC-ESI-MS). Firstly, the antihealth properties (toxicity, allergenicity) of the peptides were estimated based on the peptide sequences. Next, their health-promoting potential was demonstrated based on an in silico analysis by determining their bioactivity scores (PeptideRanker). Their various biological actions were also determined using BIOPEP-UWM tools. We presented peptide sequences with properties relevant to ensuring good health and well-being, including cardiovascular system, nervous and immune systems, or their support for the maintenance of general homeostasis. We obtained information on generation of biologically active peptides in uncured beef with acid whey and it can be considered as a new knowledge as it contributes to science development of functional and nutraceutical foods. In the long term, this information can be used in designing products with desired nutritional and health-promoting properties that are important for the well-being and for preventing the occurrence of noncommunicable diseases.